The Effects of Air Flow in the Wake of a Large Vehicle on Trailing a Passenger Car - Amirnordin, S.H.; Islam, W.S.; Seri, S. M.; Ariffin, M.F.; Rahman, H. A.; Taib, I.; Mohamad, A. N.; Alimin, A. J. (Journal of Engineering and Technology (JET), 2011)
Road driving condition under drafting is known to have an influence on the aerodynamic forces of the vehicle. Large vehicles such as busses and trucks traveling at high speeds give results in the formation of a large turbulent flow in the wake region. This turbulent flow is very unsteady in nature hence its influence on the air flow within its vicinity will also be unsteady. This paper investigates the relative values of drag and lift forces acting on a passenger car trailing a large vehicle (drafting) under unsteady conditions. The simulation is conducted using Computational Fluid Dynamics software, FLUENT for a two-dimensional flow domain at Re 3.18x106 for a trailing distance of 0 to 30 meters. The unsteady effect is studied at 15 time intervals for each time step. Turbulence is simulated using the Reynolds-Average Navier Stokes (RANS) k-ε model. Results show that aerodynamically, the critical drafting distance is between three to five meters where the lowest drag is found to occur at three meters. The results show the suitable distance for drafting which may serve as useful information for vehicle fuel economy and stability.